Poor Associations Between Radiographic Tibiofemoral Osteoarthritis and Patient-Reported Outcomes at 16 Years After Anterior Cruciate Ligament Reconstruction. Issue 9 (29th September 2020) - Identeg, Fredrik; Senorski, Eric Hamrin; Svantesson, Eleonor; Samuelsson, Kristian; Sernert, Ninni; Kartus, Jüri-Toomas; Sundemo, David
Background: Radiographic tibiofemoral (TF) osteoarthritis (OA) is common in patients after anterior cruciate ligament (ACL) reconstruction at long-term follow-up. The association between radiographic OA and patient-reported outcomes has not been thoroughly investigated. Purpose: To determine the association between radiographic TF OA and patient-reported outcome measure (PROM) scores at 16 years after ACL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: This study was based on 2 randomized controlled studies comprising 193 patients who underwent unilateral ACL reconstruction. A long-term follow-up was carried out at 16.4 ± 1.7 years after surgery and included a radiographic examination of the knee and recording of PROM scores. Correlation analyses were performed between radiographic OA (Kellgren-Lawrence [K-L], Ahlbäck, and cumulative Fairbank grades) and the PROMs of the International Knee Documentation Committee (IKDC) subjective knee form, Lysholm score, and Tegner activity scale. A linear univariable regression model was used to assess how the IKDC score differed with each grade of radiographic OA. Results: Of 193 patients at baseline, 147 attended the long-term follow-up. At long-term follow-up, 44.2% of the patients had a K-L grade of ≥2 in the injured leg, compared with 6.8% in the uninjured leg. The mean IKDC score at follow-up was 71.2 ± 19.9. Higher grades of radiographic OA were significantly correlated with lower IKDC and Lysholm scores ( r = –0.36 to –0.22). Patients with a K-L grade of 3 to 4 had significantly lower IKDC scores compared with patients without radiographic OA (K-L grade 0-1). Adjusted beta values were –15.7 (95% CI, –27.5 to –4.0; P = .0093; R 2 = 0.09) for K-L grade 3 and –25.2 (95% CI, –41.7 to –8.6; P = .0033; R 2 = 0.09) for K-L grade 4. Conclusion: There was a poor but significant correlation between radiographic TF OA and more knee-related limitations, as measured by the IKDC form and the Lysholm score. Patients with high grades of radiographic TF OA (K-L grade 3-4) had a statistically significant decrease in IKDC scores compared with patients without radiographic TF OA at 16 years after ACL reconstruction. No associations were found between radiographic TF OA and the Tegner activity level.